THE INSULINOTROPIC EFFECT OF THIAZOLIDINEDIONE DERIVATIVES IN TYPE II DIABETIC MODEL, RIN-5F CELLS, AND ITS ACTION ON CULTURED HUMAN LUNG FIBROBLAST SHOWS OXYGEN FREE-RADICAL SCAVENGING ACTIVITY - S, REKHA; DIVEKAR, KALPANA; S, CHANDRASHEKHARA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Diabetes mellitus is a persistent disorder caused by deficiency in insulin production. Oxidative stress plays an important role in physiopathology of diabetes. The present research determined the antidiabetic and antioxidant effects of 5-naphthalidin thiazolidinediones derivatives. Methods: Both in vitro and in vivo experiments were carried out on diabetes induced male Swiss albino rats by single intramuscular injection of alloxan (0.15 mg/kg i.m) and IDDM-rats received 4b, 4c, or 4d (36 mg/kg, p.o). The derivatives were further subjected to insulin secretion by RIN-5F cells confirmed insulinotropic effect. In vitro antioxidant activity was evaluated using enzymatic activities on cell lines In addition, all the synthesized derivatives showed non-toxic effects against a diseased human lung fibroblast (COPD), HCC7231 (TACC CCL-96). Results: The results revealed that 4b, 4c, and 4d showed promising results by substantially lowering the blood glucose levels on 21st day of post-administration. Serum insulin levels substantially rose, suggesting that derivatives exert insulinotropic effects through different pathways. 4c showed oxygen free-radical scavenging activity. Conclusion: Our study proves that oral administration of 5-naphthalidin-TZD twice a day is a valuable treatment for type II diabetes. It seems to be a good drug moiety endowed significant oxygen free-radical scavenging activity.